Potensi Rekayasa Kayu Pada Bangunan Green Architecture - I Putu Wikan Pithamaha; Cindy Avisha Khurniawan; I Made Pande Gosha Primayoga; Nyoman Ratih Prabandari; I Gede Surya Darmawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
Environmental problems, notably global warming, have recently emerged as a source of concern. In the world of architecture, there is a phenomenon known as "sick building syndrome," which refers to health and discomfort issues caused by poor air quality and air pollution in an occupied building, which affects residential productivity. There is also a lack of natural lighting and poor air ventilation.In addition to the existence of global warming, the development or invention of renewable energy becomes the impetus for the development of green buildings. As more people become interested in green building, timber materials become a viable option for creating a long-lasting structure. Wood has long been regarded as a sustainable material and a renewable resource. Wood may be protected in the forest by collecting naturally growing wood resources and following harvesting standards. Eco - friendly construction materials are required to decrease energy consumption, emissions, and trash or garbage in order to maintain a healthy and comfortable environment on the planet.